Liberating Researchers from the Glovebox: A Universal Thermal Radiation Protocol Toward Efficient Fully Air‐Processed Perovskite Solar Cells. Issue 5 (23rd January 2019) - Wang, Guoliang; Liu, Changwen; Kong, Weiguang; Chen, Hong; Li, Dedi; Amini, Abbas; Xu, Baomin; Cheng, Chun
Abstract : Perovskite solar cells (PSCs) have developed rapidly in the past few years. However, highly efficient PSCs prepared in ambient air have remained intractable, since the crystallization and film morphology of perovskite are highly sensitive to moisture. Here, a thermal radiated hot‐cast method (THCM) to prepare high quality perovskite films in ambient air is introduced. The proposed THCM not only eliminates the temperature gradient across the perovskite film, but also forms a significantly reduced and constant relative humidity field at the local space above the substrate (ca. 6%); these conditions result in a smooth, compact, oriented perovskite film with largely reduced grain boundaries. THCM is a universal protocol, based on the application to the devices with both inverted and regular architectures, and it enables improved J–V performance with largely reduced hysteresis. The champion power conversion efficiencies of 17.2% for inverted and 19.1% for regular devices are achieved by THCM. These are comparable to the top efficiencies of fully air‐processed PSCs, demonstrating that THCM is a promising protocol for commercialization of PSCs in the near future. Abstract : A novel thermal radiated hot‐cast method (THCM) is specially designed to fabricate highly efficient perovskite solar cells (PSCs) in ambient air. THCM creates constant temperature and ultralow relative humidity fields for perovskite growth, and is a universal protocol suitable for both inverted and regular PSCs, of which the champion power conversion efficiency of 17.2 and 19.1% is achieved, respectively.